2013
DOI: 10.1091/mbc.e13-05-0273
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic TBX3 is a downstream target and mediator of the TGF-β1 signaling pathway

Abstract: Overexpression of the developmentally important T-box transcription factor TBX3 inhibits proliferation but promotes the migration of epithelial cells. TBX3 is transcriptionally up-regulated by the TGF-β1 signaling pathway in a Smad3/4- and JunB-dependent manner and is a key mediator of the antiproliferative and promigratory roles of TGF-β1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…Furthermore, ectopic overexpression of TBX3 in non-invasive WM1650 radial growth phase (RGP) melanoma cells and the upregulation of TBX3 by RA in vertical growth phase (VGP) melanoma cells reduced the proliferative capacity of the cells with the former being associated with an increase in migratory ability (58,59). It is important to note that Transforming growth factorbeta (TGF-β) contributes to breast cancer progression by inhibiting cell proliferation and promoting migration and recent studies have shown that TBX3 is required for the anti-proliferative and pro-migratory effects of TGF-β in breast epithelial cells (60,61). The mechanism(s) that determines whether TBX3 functions as a proproliferative or anti-proliferative factor is not known.…”
Section: Tbx3 In Senescence Apoptosis and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ectopic overexpression of TBX3 in non-invasive WM1650 radial growth phase (RGP) melanoma cells and the upregulation of TBX3 by RA in vertical growth phase (VGP) melanoma cells reduced the proliferative capacity of the cells with the former being associated with an increase in migratory ability (58,59). It is important to note that Transforming growth factorbeta (TGF-β) contributes to breast cancer progression by inhibiting cell proliferation and promoting migration and recent studies have shown that TBX3 is required for the anti-proliferative and pro-migratory effects of TGF-β in breast epithelial cells (60,61). The mechanism(s) that determines whether TBX3 functions as a proproliferative or anti-proliferative factor is not known.…”
Section: Tbx3 In Senescence Apoptosis and Proliferationmentioning
confidence: 99%
“…Similar to TBX3, TGF-β1 signalling is critical for the development of the mammary glands but also contributes to breast cancer progression through the inhibition of cell proliferation and promotion of migration (93). Importantly, Li et al demonstrated that TGF-β1 treatment transcriptionally upregulated TBX3 in breast epithelial and keratinocyte cells (61). They showed that JunB and Smad4 mediate this effect and directly bind to the TBX3 promoter at a degenerate Smad Binding Element (SBE).…”
Section: Transforming Growth Factor-beta 1 (Tgf-β1) Signalling Pathwaymentioning
confidence: 99%
“…We recently reported that TGF-␤1 up-regulates expression of the T-box transcription factor, TBX3, through a mechanism involving the co-operation of Smad proteins and JunB. This was shown to be a critical downstream event for mediating TGF-␤1-induced anti-proliferation and pro-migration of breast epithelial cells and keratinocytes but the TBX3 target genes responsible for this were not described (7).…”
mentioning
confidence: 99%
“…On the other hand, overexpression of TBX3 is associated with several cancers, but it may mediate the anti-proliferative and pro-migratory role of TGF-β1 in breast epithelial and skin keratinocytes [31]. Recently it was shown that the knockdown of PLCε gene, which enhances bladder cancer cell invasion, is induced E-cadherin expression and decreased TBX3 expression, both of which were dependent on PKCα/β activity [32].…”
Section: Hypoxia As Well As the Endoplasmic Reticulum Stress Are Impomentioning
confidence: 99%
“…Thus, the induction of TBX3 gene expression may contribute to the suppression of cell proliferation and glioma growth from these cells, because TBX3 is a transcriptional repressor, which controls cell proliferation as well as mediates cellular signaling pathways [23,31]. It is interesting to note that the transcription factor TBX3 has pleiotropic functions and plays multiple roles in normal development and disease by either repressing or activating transcription of target genes in a context-dependent manner, and it may mediate the antiproliferative role of TGFB1 [31]. Thus, the increased expression of TBX3 can mediate the inhibition of cell proliferation upon ERN1 inhibition.…”
Section: Fig 1 Effect Of Hypoxia On the Expression Of Hoxc6 (Homeobmentioning
confidence: 99%